GABA spectra and remote distractor effect in progressive supranuclear palsy: A pilot study - Bonnet, C; Rusz, J; Hanuška, J; Dezortová, M; Jírů, F; Sieger, T; Jech, R; Klempíř, J; Roth, J; Bezdíček, O; Serranová, T; Dušek, P; et al. (Revue neurologique, 2017)
Disturbances of the gamma-aminobutyric-acid (GABA) system have been suspected of contributing to the pathophysiology of progressive supranuclear palsy (PSP). The ability to rapidly resolve competitive action decisions, such as shifting the gaze to one particular stimulus rather than another, can be predicted by the concentration of GABA in the region of the frontal cortex relevant to eye movements. For this reason, our study measured GABA levels in seven PSP patients and eight healthy controls, using proton magnetic resonance spectroscopy, and assessed the relationship of these measurements to the remote distractor effect (RDE), an eye-movement paradigm investigating competitive action decisions. No significant differences were found in either frontal-eye-field GABA levels or RDE between PSP patients and controls.
Keywords: Magnetic Resonance Imaging; Prefrontal Cortex; magnetická rezonanční tomografie; pohyby očí; prefrontální mozková kůra; zraková pole; Humans; Healthy Volunteers; lidé středního věku; Eye Movements; Female; Aged; okulomotorické svaly; progresivní supranukleární obrna; Magnetic resonance; senioři; lidé; Progressive supranuclear palsy; magnetická rezonanční spektroskopie; Photic Stimulation; Supranuclear Palsy, Progressive; světelná stimulace; pilotní projekty; Pilot Projects; Spectroscopy; Oculomotor Muscles; Saccades; ženské pohlaví; Male; Middle Aged; sakadické oční pohyby; gamma-Aminobutyric Acid; GABA; Distraction; zdraví dobrovolníci pro lékařské studie; Magnetic Resonance Spectroscopy; Visual Fields; mužské pohlaví; Eye movements